When Public Recognition Inhibits Prosocial Behavior: The Case of Charitable Giving. (October 2020) - Denis, Etienne; Pecheux, Claude; Warlop, Luk
Commonly regarded as an important driver of donation behavior, public recognition also can reduce donations. With three studies, this research manipulates whether donors receive public, private, imposed, or optional forms of recognition; the results show that the influence of recognition on the decision to donate is moderated by donors' need for social approval. Whereas public recognition improves charitable giving among people with higher need for approval, imposing recognition reduces donations among people with lower need, suggesting a potential crowding-out effect on prior motives (Study 1). This penalty for public recognition disappears when the public recognition is optional (Study 2). When public recognition is saliently imposed (not requested), donation likelihood increases, suggesting that donors' potential concerns about observers' suspicion of their true motives is reduced (Study 3). This research highlights conditions in which public recognition encourages charitable giving and paves the way for further research on social dimensions of generosity.